Kajian Hukum Pelanggaran Kewenangan Notaris Dalam Membuka Kantor Cabang Untuk Jasa Hukum Dikaitkan dengan Kode Etik Notaris - R. Yuniar Anisa Ilyanawati; Tasya Aurellya; Irnie Wahida Putri; Tetti Samosir (Universitas Djuanda, 2025)
The purpose of this research is to analyze violations of notary authority in opening branch offices for legal services that are not in accordance with the Notary Code of Ethics and Law Number 30 of 2004 juncto Law Number 2 of 2014 concerning the Position of Notaries (UUJN), which is suspected of violating the principles of authority and accountability, even though it is explicitly prohibited by UUJN. This research method uses a normative juridical method with a statutory approach and analysis of the Notary's Code of Ethics. The research results show that the opening of a branch office by a notary violates the applicable provisions in the UUJN and the Notary Code of Ethics, which aim to maintain the integrity and accountability of the profession. The conclusion of this research states that the act of opening a branch office is contrary to the principles of notary professionalism and can result in legal and ethical sanctions. The suggestion put forward is the importance of increasing supervision by the Indonesian Notary Association (INI) and stricter law enforcement to prevent similar violations in the future.